IT skills : requirements for employed persons - Hall, Anja [Verfasser] (My University, 2024)
"IT skills are among the key competencies needed to meet the (future) challenges of the world of work. While there is a consensus on the importance of IT skills, robust empirical analyses of their diffusion remain scarce. Based on the 2024 BIBB/BAuA Employment Survey, this article shows which IT skills are currently required in the workplace and how the IT skill requirements differ depending on the job’s level of complexity." (BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 2.3.4 Qualifikationswandel; 370; Arbeitswelt; Qualifikationsanforderung; IT-Kompetenz; Digitalkompetenz; BIBB/BAuA-Erwerbstätigenbefragung